A base-free terminal thorium phosphinidene metallocene and its reactivity toward selected organic molecules. Issue 7 (28th January 2019) - Zhang, Congcong; Hou, Guohua; Zi, Guofu; Walter, Marc D.
Abstract : Small molecule activation mediated by a base-free terminal phosphinidene thorium metallocene is reported. Abstract : The stable base-free terminal phosphinidene thorium metallocene, [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 ThP-2, 4, 6- t Bu3 C6 H2 (2 ), can be isolated from the reaction of the thorium dichloride complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 ThCl2 (1 ) with 2 equiv. of 2, 4, 6-(Me3 C)3 C6 H2 PHK in THF. The reactivity of2 in the activation of various small organic molecules such as diselenides, phosphines, imines, ketones, phosphine oxides, thiazole, imidazole derivatives and amines was explored. For example, when complex2 is treated with Ph2 Se2, the phosphinidene is replaced, yielding diselenido compound [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th(SePh)2 (3 ). Moreover, E–H (E = P, N, C) bond activation occurs on exposure of2 to 2, 4, 6- i Pr3 C6 H2 PH2, PhPH2, ( p -tolyl)2 CNH, 1-indanone, cyclohexanone, Me3 PO, thiazole, 1-methylimidazole and p -toluidine, resulting in the phosphido complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ][η 5, κ- C -1, 2-(Me3 C)2 -4-(CH2 CMe2 )C5 H2 ]Th(PH-2, 4, 6- i Pr3 C6 H2 ) (4 ), the metallaheterocycle [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th(η 2 -P2 Ph2 ) (5 ), the iminato phosphido complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th(PH-2, 4, 6- t Bu3 C6 H2 )[NC( p -tolyl)2 ] (6 ), the phosphido enolyl compound [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th(PH-2, 4, 6- t Bu3 C6 H2 )(κ- O -1-OC9 H7 ) (7 ), the enolyl complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ][η 5, κ- C -1, 2-(Me3 C)2 -4-(CH2 CMe2 )C5 H2 ]Th(κ- O -1-OC6 H9 ) (8 ), the alkyl complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ][η 5, κ- C -1, 2-(Me3 C)2 -4-(CH2 CMe2 )C5 H2 ]Th(κ- O, C -OPMe2 CH2 ) (9 ), the phosphido thiazolyl complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th(PH-2, 4, 6- t Bu3 C6 H2 )(C3 H2 NS) (10 ), the bis-imidazolyl complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 Th[2-(1-MeC3 H2 N2 )]2 (11 ), and the imido complex [η 5 -1, 2, 4-(Me3 C)3 C5 H2 ]2 ThN( p -tolyl) (12 ), respectively. Several spectroscopic techniques were employed for the characterisation of the new complexes3–11, and in addition the solid-state molecular structures of compounds3–6, 8–9 and11 were further confirmed by X-ray diffraction analyses.